Listeriolysin O-based serodiagnosis of listeriosis and vis-à-vis cultural isolation of Listeria monocytogenes in slaughtered goats - Suryawanshi, Rahul; Chaudhari, Sandeep; Shinde, Shilpshri; Kurkure, Nitin; Khan, Wiqar; Shelke, Dnyaneshwar; Bharate, Sachin (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was undertaken to ascertain prevalence, pathogenicity vis-a-vis seroprevalence of L. monocytogenes among goats slaughtered at Nagpur. The organism was isolated, identified, and characterized following USDA protocol from a total of 202 samples comprising blood samples (101) and chevon samples (101) revealing 1.98% prevalence of pathogenic L. monocytogenes. The virulent nature of pathogenic Listeria isolates was also assessed by in-vitro tests like haemolysis on sheep blood agar, CAMP test and PI-PLC assay. Listeriolysin O (LLO) protein produced by L. monocytogenes was purified employing ion-exchange chromatography. The purity of the LLO was confirmed using SDS-PAGE, which revealed it to be a homogeneous 58 kDa protein. Hyper immune serum was raised against purified LLO in healthy rabbits. An ELISA was standardise by the checker-board titration method and using LLO as an antigen and anti-LLO antibodies in raised hyper immune serum. The LLO-based indirect ELISA screening of streptolysin-O adsorbed sera from slaughtered goats demonstrated seropositivity for ALLO in 13.86% samples. Moreover, in this study, a positive correlation between seropositivity and isolation of pathogenic L. monocytogenes from the same animal was also noted endorsing the active functioning of ALLO in infection control. The results advocate use of LLO-based indirect ELISA on SLO adsorbed sera for rapid and reliable serodiagnosis of listeriosis in large populations where traditional isolation methods are not feasible.